2003
DOI: 10.1191/0961203303lu421cr
|View full text |Cite
|
Sign up to set email alerts
|

Water intoxication induced by low-dose cyclophosphamide in two patients with systemic lupus erythematosus

Abstract: Cyclophosphamide (CY) is an alkylating agent used to treat a variety of autoimmune disorders. Water intoxication is a well-known complication of high-dose intravenous (i.v.) CY, but is rare in patients treated with low dose i.v. CY. We describe two patients with lupus nephritis and water intoxication following low dose i.v. CY. The first patient was treated with oral prednisolone and azathioprine for eight weeks with inadequate response and persistent renal inflammatory activity. Eight hours after the first i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…A low dose of oral cyclophosphamide used in the treatment of some rheumatic diseases or autoimmune glomerulonephritis can cause WI. One or more cyclophosphamide metabolites may directly alter water permeability in the kidney leading to DI [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A low dose of oral cyclophosphamide used in the treatment of some rheumatic diseases or autoimmune glomerulonephritis can cause WI. One or more cyclophosphamide metabolites may directly alter water permeability in the kidney leading to DI [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Even low-dose cyclophosphamide may induce hyponatremia in patients with systemic lupus erythematosus [28,29]. Probably less known is that hyponatremia has also been attributed to several new substances (tyrosine kinase inhibitors and antibodies) used in today's targeted oncologic treatment (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…6 However, as listed in Table 1, patients with water intoxication associated with lower doses of CY have been reported since the 1980s, probably due to the increasing numbers of patients receiving low to moderate doses of CY which targets nonmalignant disorders such as rheumatic diseases. [10][11][12][13][14] Bressler and Huston first reported that water intoxication developed after a moderate dose of CY in a patient with systemic lupus erythematosus. 10 Webberley and Murray reported a patient with multiple myeloma, in whom water intoxication developed following treatment with oral indomethacin and lowdose IVCY.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Recently, lifethreatening water intoxication was also reported to occur even by low (10 mg/kg) to moderate (15-20 mg/kg) doses of CY applied to treat rheumatic disorders. [10][11][12][13][14] Here, we describe a patient with polyarteritis nodosa demonstrating water intoxication after administration of IVCY at a moderate dose.…”
Section: Introductionmentioning
confidence: 99%